RELEVANCE OF KAKOLI (ONE AMONG ASTAVARGA) IN ANCIENT AYURVEDIC TREATISE ALONG WITH ETYMOLOGY OF ITS VARIOUS SANSKRIT SYNONYMS - Kumar Vijay; Mishra Rajesh Kumar*; Gupta Ankita; Srivastava Anupam (AYUSHDHARA, 2020)
The knowledge about medicinally useful plants in the early age is scientifically documented, and systematically organized in Ayurveda Samhitas, Nighantus and other texts. The ancient nomenclature of Ayurvedic herbs was not only useful for their identification but also to know their medicinal values for example, Payasvinī means galactogogue, Kākolī means which contains high moisture value, Madhurā means Madhura in Rasa, etc. Moreover, our Acharyas also suggested different names of the Ayurvedic herbs based on their habits, taxonomy and uses. Though the modern science is successful in classifying the flora taxonomically, but could not reach up to the ground breaking concept of classifying plants according to their medicinal properties. Being aware of taxonomic aspects of nomenclature along with the torch of synonyms coined by ancient seers one may be able to preserve the treasury traditional medicinal knowledge. Kākolī has been mentioned as one of the Aṣṭavarga plants. Kākolī has also been documented in the various Saṁhitā and Nighaṇṭu. Description of Kākolī along with its Sanskrit synonyms, habitat and medicinal properties has also been mentioned in different Nighaṇṭu. However, due to the lack of appropriate taxonomic data, mainly three plant species i.e., Roscoea purpurea Sm., Roscoea capitata Sm. and Roscoea alpina Royle are widely accepted as Kākolī. The main objective of this study was to critically review the Sanskrita name of Kākolī described in classical Ayurvedic literature along with medicinal properties.